Genome sequencing and annotation of Aeromonas sp. HZM - Patric Chua (Genomics Data, 2015)
We report the draft genome sequence of Aeromonas sp. strain HZM, isolated from tropical peat swamp forest soil. The draft genome size is 4,451,364 bp with a G + C content of 61.7% and contains 10 rRNA sequences (eight copies of 5S rRNA genes, single copy of 16S and 23S rRNA each). The genome sequence can be accessed at DDBJ/EMBL/GenBank under the accession no. JEMQ00000000.